2020
DOI: 10.1002/jcsm.12596
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell deconstruction of post‐sepsis skeletal muscle and adipose tissue microenvironments

Abstract: Background Persistent loss of skeletal muscle mass and function as well as altered fat metabolism are frequently observed in severe sepsis survivors. Studies examining sepsis-associated tissue dysfunction from the perspective of the tissue microenvironment are scarce. In this study, we comprehensively assessed transcriptional changes in muscle and fat at single-cell resolution following experimental sepsis induction. Methods Skeletal muscle and visceral white adipose tissue from control mice or mice 1 day or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 58 publications
(86 reference statements)
1
35
0
Order By: Relevance
“…In a mouse model of peritonitis-induced sepsis with concomitant loss of adipose tissue and muscle mass, single-cell RNA sequencing analysis revealed that macrophage populations increase in muscles and decrease in adipose tissue 1 day after intraperitoneal injection of faecal slurry 76 . This was coupled with an increase in the levels of muscle-infiltrating neutrophils, natural killer cells and T cells that remained elevated in both the muscle and the adipose tissue 1 month after injection.…”
Section: Immune Cells In Cachexiamentioning
confidence: 99%
“…In a mouse model of peritonitis-induced sepsis with concomitant loss of adipose tissue and muscle mass, single-cell RNA sequencing analysis revealed that macrophage populations increase in muscles and decrease in adipose tissue 1 day after intraperitoneal injection of faecal slurry 76 . This was coupled with an increase in the levels of muscle-infiltrating neutrophils, natural killer cells and T cells that remained elevated in both the muscle and the adipose tissue 1 month after injection.…”
Section: Immune Cells In Cachexiamentioning
confidence: 99%
“…Inflammation-associated skeletal muscle wasting occurs in cancer cachexia and sepsis-induced skeletal muscle atrophy and significantly affects patient morbidity and mortality. Due to a lack of effective treatment options [ 54 , 55 ], this study aimed to investigate the potential of LiCl in treating inflammation-associated skeletal muscle wasting using in vitro and in vivo models of cancer cachexia and sepsis. We found that LiCl increased muscle mass, enhanced muscle strength, and increased fiber cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
“…These transcripts are associated with cancer-associated muscle wasting in humans (25)(26)(27), but like myofiber rounding, are not typically linked to murine cancer-associated muscle wasting (Figure 2D). We next performed validated pathway and regulator analyses (28)(29)(30)(31) and prioritized several candidate compounds predicted to reverse the aged muscle-specific atrophy signature (Figure 2E). 18 compounds were exclusively identified in the aged dataset (Figure 2F).…”
Section: Transcriptomic Analyses Identify 3-ma As a Candidate Mediator Of Muscle Wastingmentioning
confidence: 99%